PENCIPTAAN ACTION FIGURE SUPERHERO - RAHMI IKHLASIAH, Drs. Erfahmi,M.Sn, Drs. Yusron Wikarya, M. Pd (Serupa The Journal of Art Education, 2015)
The purpose of this final assignment/scription is to visualize superhero characters in action figure form that had been created by writer. By casting technique, writer creates three superhero characters that are Kapten Milo, Aries, and AngkasaResah, each of them is created in the form of normal human anatomy, chibi form and in the form of capsules. From these superhero characters, it provides some action figures of superhero that are: Kapten Milo, Kapten Milo Chibi, Kapten Milo Hunt, Milo Cahaya Bulan, Kapsul Kapten Milo, Kapsul Milo Hunt, Kapsul Milo Cahaya Bulan, Aries, Chibi Aries, Badai Aries, Aries Pelangi Hitam, Kapsul Aries, Kapsul Badai Aries, Kapsul Aries Pelangi Hitam, Angkasa Resah, R-Resah, Ultimate Resah, dan Kapsul Angkasa Resah, Kapsul R-Resah, Kapsul Ultimate Resah. The third character of the superhero Kapten Milo, Aries, and Angkasa Resah appear as heroes who protect and save people from a group of evilwhere come from the criminal organization.Kata Kunci: Superhero, Action Figure, Teknik Casting